Respuesta :

DeanR

2.5x - 3 + 2x = 1.75x - 1.25x + 13

4.5x - 3 = 0.50x + 13

4.0x = 16

x = 4

Answer: 4

2. We'll assume those xs are in the numerator

(3/7)x - 1/4 + (3/7)x = (9/7)x - (3/7)x + 3/4 - 1

(6/7)x - 1/4 = (6/7)x  - 1/4

0 = 0

That's always true.

Answer: Any x is a solution.

Answer:

2.5x - 3 + 2x = 1.75x - 1.25x + 13

4.5x - 3 = 0.50x + 13

4.0x = 16

x = 4

Answer: 4

2. We'll assume those xs are in the numerator

(3/7)x - 1/4 + (3/7)x = (9/7)x - (3/7)x + 3/4 - 1

(6/7)x - 1/4 = (6/7)x  - 1/4

0 = 0

That's always true.